163k views
1 vote
PLEASE AM BEGGINNN YOUUUUU

PLEASE AM BEGGINNN YOUUUUU-example-1

1 Answer

5 votes

Answer:

Explanation:

A)

A - the population after its decrease

x - the number of years in which there has been a decrease in population

Hence,


\displaystyle\\A=30000-475x\\A+475x=30000-475x+475x\\A+475x=30000\\A+475x-A=30000-A\\475x=30000-A

Divide both parts of the equation by 475:


\displaystyle\\x=(30000-A)/(475)

B)


\displaystyle\\x=(30000-24300)/(475) \\\\x=(5700)/(475)\\\\x=(12*475)/(475) \\\\x=12\ years

User Jhvaras
by
5.9k points